Engineering science - Bolton, W. (William), 1933- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Engineering Science is a comprehensive textbook suitable for all vocational and pre-degree courses, being fully in line with the latest vocational courses at Level 2 and leading into Level 3"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering; Mechanical engineering; Electrical engineering; TECHNOLOGY / Engineering / General; TECHNOLOGY / General; TECHNOLOGY / Electricity